Thematic Study of Suratul-Muṭaffifin, with Particular Reference to Business Transactions among Muslim Traders in Ilorin - Adam Sambo (Indonesian Journal for Islamic Studies, 2025)
Background of study: Surātul-Mutaffifin is a chapter in the Glorious Qu'rān which concentrates more on the condemnation of unethical practice in business transaction at the instance of reduction in weight and measurement.Aims and scope of paper: This work looks into the thematic content of the Sūrah in connection to unethical practices in business transactions among Muslim traders in Ilorin metropolis.Methods: Oral interview is used in gathering information in the work. The methods employed are descriptive and analytical. While the former is deployed to highlight the existing business engagements in Ilorin, the latter is considered for explaining the manner in which fraudulent practice is prevalent among the Muslim traders in those areas of business engagements.Results: The finding of the work shows that many of the Muslim traders do engage in fraudulent activities consciously in flagrant disregard for the principle of Sharī'ah on commercial activities. Conclusion: While the work concluded that unawareness of the eschatological implication of such practice is a factor that needs to be addressed. Recommendations followed that institution of Hisbah board by government in the state and setting up of task force to complement the efforts of Islamic preachers in the domain will have a great impacts in curtailment of ungodly practice among the concerned Muslim traders.